Antibiotic treatment and risk of gastric cancer. Issue 6 (21st March 2006) - Fall, K; Ye, W; Nyrén, O
Abstract : Background/aims: Helicobacter pylori infection is undoubtedly an important risk factor for gastric cancer. It remains unclear however whether antibiotic treatment may prevent gastric cancer development. Our aim was to assess long term gastric cancer risks in historic cohorts of patients presumed to have been heavily exposed to antibiotics. Subjects: Using the Swedish Inpatient Register, we identified 501 757 individuals discharged with any one of 10 selected infectious disease diagnoses between 1970 and 2003. Methods: We counted person time and non-cardia gastric cancer occurrences through linkage to virtually complete population and health care registers. Standardised incidence ratios (SIRs) were calculated for comparisons with cancer incidence rates of the general population in Sweden. Results: No reduction in gastric cancer risk was observed in the infectious disease cohort in total (SIR 1.08 (95% confidence intervals 1.00–1.17) or for any of the presumed antibiotic regimens. There were no clear trends towards decreasing risk with time of follow up, but the risk tended to fall with increasing age at first hospitalisation for the infection (p<0.04). Conclusions: Our results do not confirm earlier observational findings of a reduced risk of gastric cancer following exposure to heavy antibiotic treatment among hip replacement patients. Suboptimal drug regimens, inadequate timing of H pylori eradication, or insufficient follow up time may possibly explain the lack of association in this setting. Although our findings do not rule out the cancer preventive potential of H pylori eradication, they emphasise that detection of such an effect, if any, may require considerable efforts.